1998
DOI: 10.1103/physreve.58.6015
|View full text |Cite
|
Sign up to set email alerts
|

Chiral patterns arising from electrostatic growth models

Abstract: Recently, unusual and strikingly beautiful seahorse-like growth patterns have been observed under conditions of quasitwo-dimensional growth. These 'S'-shaped patterns strongly break two-dimensional inversion symmetry; however such broken symmetry occurs only at the level of overall morphology, as the clusters are formed from achiral molecules with an achiral unit cell. Here we describe a mechanism which gives rise to chiral growth morphologies without invoking microscopic chirality. This mechanism involves tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…Moreover, TEM examinations of different samples, prepared simultaneously with or without applied electric field (0−10 3 V/cm), showed that there are no obvious difference among the patterns of them. Therefore, contrary to the reported electrostatic growth models, 21 we conclude that charged clusters are unnecessary to the chiral pattern formation.…”
contrasting
confidence: 44%
See 1 more Smart Citation
“…Moreover, TEM examinations of different samples, prepared simultaneously with or without applied electric field (0−10 3 V/cm), showed that there are no obvious difference among the patterns of them. Therefore, contrary to the reported electrostatic growth models, 21 we conclude that charged clusters are unnecessary to the chiral pattern formation.…”
contrasting
confidence: 44%
“…16−19 Recently, it was reported the observation of quasi-twodimensional chiral patterns in growth of C 60 -TCNQ by an ionized-cluster-beam (ICB) method. 20 Theoretical investigations have also been carried out on the broken symmetry of these patterns, 21 where, motivated by the presence of electric charged clusters in ICB deposition, the charged clusters are considered to be the crucial role that determines the chiral pattern formation. However, the actual growth mechanism and the role of charged clusters are still under debate.…”
mentioning
confidence: 99%
“…Referring to Ref. 16 for details, we here note simply that, for one set of assumptions which gave promising results, we obtain growth at a point (x, y) in the boundary of a growing island proportional to exp[χ|E(x, y)| 2 /2kT ] (where T is a temperature appropriate to the diffusing clusterswhich may be higher than the substrate temperature T s ).…”
Section: Modeling and Simulationmentioning
confidence: 81%
“…A detailed description of this modeling work is given in Ref. 16. The models studied include deterministic and nondeterministic "tree" growth models 31 ; Monte-Carlo (MC) simulations 32 of diffusive aggregation; and a continuum model for the motion of the island boundary.…”
Section: Modeling and Simulationmentioning
confidence: 99%
See 1 more Smart Citation